Exosomal lnc‐AFTR as a novel translation regulator of FAS ameliorates Staphylococcus aureus‐induced mastitis. (2nd December 2021) - Chen, Yu; Yang, Jing; Huang, Zhi; Jing, Hongyuan; Yin, Baoyi; Guo, Shuai; Deng, Ganzhen; Guo, Mengyao
Abstract: Although the specific expression of long noncoding RNA (lncRNA) in mastitis tissue has been reported, few studies have involved the differential expression of lncRNA in mastitis exosomes (Exo) and its mechanism and function. We screened an lncRNA associated with FAS translational regulation (lnc‐AFTR) through exosomal RNA sequencing, and clarified its function and molecular mechanism. Lnc‐AFTR is markedly downregulated in Staphylococcus aureus ‐Exo and S. aureus ‐induced MAC‐T cell as well as mastitis tissue. Overexpression of lnc‐AFTR exosomes (oe‐AFTR‐Exo) significantly improves cell damage induced by S. aureus, including inhibiting apoptosis, promoting proliferation, and increasing the production of pro‐inflammatory cytokines (tumor necrosis factor‐α [TNF‐α] and interleukin‐1β [IL‐1β]). Oe‐AFTR‐Exo also suppressed the activation of Caspase‐8, Caspase‐3, and JNK. Dual‐luciferase report analysis confirmed that lnc‐AFTR interacts with FAS mRNA directly to hinder translation process, but does not degrade FAS mRNA. Overexpression of lnc‐AFTR in MAC‐T cells obviously reduced S. aureus ‐induced apoptosis and inflammation. Knockdown of lnc‐AFTR significantly increased FAS and promoted the activation of Caspase‐8, Caspase‐3, and JNK caused by S. aureus . In summary, these results revealed the mechanism by which lnc‐AFTR directly bound FAS mRNA to prevent translation, and confirmed that the exosomal lnc‐AFTR exerted anti‐inflammatory and anti‐apoptotic effects by inhibiting the activation of TNF signaling pathway and mitogen‐activated protein kinases (MAPK) signaling pathway.